Sistem Pendeteksi Polusi Udara di Kota Bandar Lampung Menggunakan Teknologi Internet of Things (IoT) - Muhammad Iqbal; Bambang Hermanto; Febi Eka Febriansyah; Muhammad Ridho (Jurnal Komputasi, 2019)
Bandar Lampung City is the centre of the economy, services and trade in Lampung Province so that a healthy city environment needs to be kept clean and comfortable to support people's lives in carrying out daily activities. One factor that affects the cleanliness and comfort of the city of Bandar Lampung is the condition of air quality in the city of Bandar Lampung. The number of vehicles and industrial factories in the city of Bandar Lampung has become a major factor affecting air quality, such as the increase in harmful pollutant gases such as carbon monoxide gas (CO) and carbon dioxide (CO2), dust (PM10), nitrogen dioxide gas (NO2) and sulfur dioxide gas (SO2).Pollutant gas monitoring is one of the solutions in creating good air quality for the community. One of them is by utilizing information and communication technology. One of the utiliparameterion of information and communication technology in air quality monitoring is to use Wireless Sensor Network (WSN). WSN technology, which is the technology used to distribute and acquire data that is monitored and controlled centrally. This research builds an air pollution monitoring system in Bandar Lamping City by utilizing WSN and GSM technology for wireless data transmission to server applications. The results of this study are air pollution monitoring systems running well by displaying the outputs of sensor node acquisition based on the parameters of carbon monoxide (CO), dust (PM10), nitrogen dioxide (NO2) and sulfur dioxide (SO2) gases. The results of the calculation of the average overall sensor nodes for each parameter are 49 μg / m3 for PM10 substances, 34 μg / m3 for SO2 substances, 24 μg / m3 for NO2 substances, and 25 μg / m3 for CO substances. Based on the ISPU index and category, the results are in a good category. This means that the condition of air quality in the city of Bandar Lampung in the good category.